Role of Na2CO3 on an AISI 330 austenitic stainless steels oxidation at 900°C. Issue 8 (26th March 2019) - Buscail, Henri; Issartel, Christophe; Riffard, Fréderic; Perrier, Sébastien; Rabaste, Francoise; Poble, Olivier; Combe, Cécile
Abstract: This study shows the influence of sodium carbonate coatings on the austenitic AISI 330 (Fe–35Ni–19Cr–1.3Si) oxidized during 48 hr at 900°C. The N2 ‐5 vol% H2 gaseous environment was used to simulate industrial heat treatment conditions. Silica scale formation is promoted by low oxygen‐containing gaseous environments and the high alloy silicon content. On this alloy, an amorphous silica scale is formed after the blank material oxidation. It indicates that silicon is free to diffuse in the alloy and forms a silica scale at the internal interface. On Na2 CO3 ‐coated specimens, no silica scale is formed. Then, sodium combines with silicon to form amorphous glass particles. A comparison has been performed with results obtained on a AISI 330Cb niobium containing alloy in the same oxidizing conditions. It is then concluded that sodium carbonate coatings could only favor silica formation on niobium containing alloy due to a reaction between sodium and niobium. Abstract : On blank AISI 330, amorphous SiO2 formation is due to silicon diffusion from the alloy to the internal interface. On Na2 CO3 ‐coated specimens, no silica scales are formed because niobium is not present to combine with sodium. Then, silicon reacts with sodium to form amorphous glass particles. Sodium carbonate coatings only favor silica formation on niobium containing alloys due to a possible neutralization of sodium by niobium.